Incidental gynaecological malignancy in women who underwent hysterectomy for utero-vaginal prolapse: a 3-year institutional case study - Seles, Fathima M.; Indira, Rajavelu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pelvic organ prolapse is common is almost 50% of women over the age of 50years. The objective of the present study was to estimate the number of incidental gynaecological malignancies in women who underwent hysterectomy for utero-vaginal prolapse. Methods: 354 women who presented with asymptomatic utero-vaginal prolapse were included in this study. Women who were symptomatic with bleeding per vaginum, lower abdominal pain or excessive white discharge and preoperative screening tests such as VIA/VILI, colposcopy, Pap smear and radio-imaging showing any gynaecological lesions were excluded from this study. Results: Histopathological examination of the hysterectomy specimen showed premalignant lesion in 13 cases accounting to 3.7% (11 cases of CIN I, 1 case of CIN II, 1 case of CIN III) and malignant lesions in 5cases accounting for 1.4% (4 cases of endometrial adenocarcinoma and 1 case of cervical squamous cell carcinoma). Conclusions: Asymptomatic women with utero-vaginal prolapse may have pre-existing premalignant and malignant lesions. Therefore, all women undergoing hysterectomy should be preoperatively screened with transvaginal ultrasound, endometrial biopsy and pap smear to rule out malignancy, as the management differs for patients with co-existing gynecological malignancies.